Chronic hepatitis C virus infection: Relationships between inflammatory marker levels and compensated liver cirrhosis - Li, Xu (Medicine (Baltimore), 2019)
We investigated associations between inflammatory marker levels and hepatitis C virus (HCV)-related compensated liver cirrhosis risk in patients with chronic hepatitis C (CHC) infection in China. We used a case-control design and data from the records of 110 Chinese patients with CHC and cirrhosis for the study; 458 CHC patients who did not have a diagnosis of cirrhosis were matched to the case group by age and sex characteristics. We also investigated fatty liver disease risk factors. The group of patients with CHC infection and cirrhosis had lower platelet-to-lymphocyte ratio (PLR) values (60.63 [44.09, 89.31]) compared with the control group patients (80.24 [57.85, 111.08]). The results indicated that the group of patients with cirrhosis had higher 4-factor fibrosis index and aspartate aminotransferase (AST)-to-platelet ratio index (APRI) values compared with the group of patients with CHC-only (1.66 [0.98, 2.60] vs 0.71 [0.45, 1.17], respectively; P < .001 and 2.12 [0.97, 4.25] vs 0.99 [0.51, 2.01], respectively; P < .001). Compared with the control group, the AST/alanine aminotransferase ratio (AAR) values in the group of patients with cirrhosis were significantly higher (P < .001). Logistic regression analysis that included model adjustment for demographic characteristics and other factors that could affect cirrhosis risk revealed that greater 1/PLR values were associated with an increased odds of having cirrhosis (adjusted odds ratio [AOR], 95% confidence interval [CI] 0.991 [0.985–0.996]); APRI and AAR values were also independent predictors of the presence of compensated cirrhosis. We found that compared with the patients with CHC-only, the triglyceride, cholesterol, and low-density lipoprotein cholesterol levels in the patients with both CHC and fatty liver disease were significantly higher. The multivariate analysis of the risk of fatty liver development in patients with CHC infection found that cholesterol level was a statistically significant risk factor (AOR [95% CI] 1.380 [1.089–1.750], P = .008). Increased 1/PLR, APRI, and AAR values were associated with increased risks for development of cirrhosis in this population of Chinese patients with CHC infection. Higher cholesterol levels increased the risk of development of fatty liver disease in patients with CHC.